Neonatal sepsis-a peek into our findings in Northwest Nigeria: a prospective study - Samaha S. Mustapha; Aishatu Musa Zaidu; Nanret Tanko Azaria; Shamsudin Aliyu; Isa Abdulkadir (SpringerOpen, 2024)
Abstract Background Neonatal sepsis is still a global health concern as it contributes to a high burden of neonatal morbidity and mortality especially in developing countries. The aim of the study is to give an insight into neonatal sepsis: risk factors, sepsis types, clinical features, pathogen burden with their antibiotic sensitivities, and outcome of admission in our facility. The study was a prospective hospital-based study conducted over 10 months, October 2018-July 2019. Result Of the 248 term neonates with features of sepsis enrolled in the study 94 (37.9%) were confirmed to have sepsis. Late-onset sepsis LOS (68%) was found to be the most common, and most of the neonates were delivered elsewhere. Clinical features were non-specific for both early-onset (EOS) and LOS and include fever, jaundice, poor suck, and depressed primitive reflexes. Infections were mostly caused by gram-negative bacteria, and while Staphylococcus aureus was the single most common isolate for both EOS and LOS. Antibiotic sensitivity was highest with ciprofloxacin for both EOS and LOS. Mortality was high at 14.9% and was mostly contributed to by Staphylococcus aureus infection. Conclusion Neonatal sepsis is still a burden with mostly non-specific clinical features. The local prevalent organisms were Staphylococcus aureus, Enterobacter agglomerans and Klebsiella pneumonia with good antibiotic susceptibility to ciprofloxacin. Most presented with late-onset sepsis and therefore infection is likely to be community-acquired which to a great extent can be prevented with robust public health interventions.